(untitled) (Journal of actual problems of jurisprudence, 2019)
This article discusses the current issues of freedom of labor. The authors examine the problems encountered in the implementation of the right to freedom of labor. The article also discusses the features of security and protection of the right to freedom of labor. The authors provide recommendations to improve the legislation of Kazakhstan in the sphere of ensuring the right to freedom of labor. Keywords: freedom of labor, right to work, contract, law, trade unions.